Training in Entrepreneurship Management for Aisyiyah Marelan-I Branch Businesses to Strengthen the Creative Economy - Rahayu, Sri Endang; Julita, Julita; Sembiring, Masta (Yayasan Rahmat Islamiyah, 2026)
Women's participation in the creative economy is very high. This industry absorbs a significant portion of the female workforce, exceeding 50% year after year. The women of Aisyiyah's Marelan I branch possess considerable human resource potential, but members still face several limitations, particularly in terms of business ideas that align with market needs, marketing strategies, and business management. They also lack the skills to master simple financial record-keeping to ensure business sustainability. The purpose of this community service is to provide skills, namely training in entrepreneurship. After the training, Aisyiyah members are expected to be able to produce several products, such as bouquets, improve the quality of existing products to increase their sales value, and develop several new businesses, including the Aisyiyah Family Economic Business Development (BUEKA). This community service activity is implemented through hands-on entrepreneurial management training, including bouquet making, online product marketing training, and simple bookkeeping training. Participants in this activity are 30 Aisyiyah branch members. Evaluation using interviews and questionnaires indicates that 90% of participants understood the training provided.